Tax systems and their assessment criteria - Abdiyeva, Nilufar; Hashimov, Pazliddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents the concepts of tax and tax systems in general. The criteria for assessing tax systems are described. Their interrelation and contradictions are considered.